Association between physical function and long-term care in community-dwelling older and oldest people: the SONIC study - Werayuth Srithumsuk; Mai Kabayama; Kayo Godai; Nonglak Klinpudtan; Ken Sugimoto; Hiroshi Akasaka; Yoichi Takami; Yasushi Takeya; Koichi Yamamoto; Saori Yasumoto; Yasuyuki Gondo; Yasumichi Arai; et al. (Komiyama Printing Co. Ltd, 2020)
Abstract Background Preventing the need for long-term care (LTC) by identifying physical function risk factors are important to decrease the LTC burden. The objective of this study was to investigate whether grip strength and/or walking speed, which are components of the frailty definition, are associated with LTC in community-dwelling older and oldest people. Methods The participants were 1098 community-dwelling older and oldest people who had not received LTC at the baseline. The endpoint was receiving LTC after the baseline survey. The independent variables were grip strength and walking speed, and participants were divided into two groups based on these variables. The confounding factors were age, sex, the Japanese version of the Montreal Cognitive Assessment (MoCA-J), hypertension, diabetes mellitus, stroke, joint diseases, living alone, body mass index, and serum albumin. We calculated the hazard ratio of receiving LTC using the Cox proportional hazard model. Results Among the 1098 participants, 107 (9.7%) newly received LTC during the follow-up. Regarding the physical function, only slow walking speed was significantly correlated with LTC after adjusting for all confounding factors except the MoCA-J score (HR = 1.74, 95% CI = 1.10-2.75, P = .018). However, slow walking speed was still a risk factor for LTC after adjusting for the MoCA-J score and other confounding factors (HR = 1.64, 95% CI = 1.03-2.60, P = .037). Conclusions The findings from this study may contribute to a better understanding of slow walking speed as a factor related to LTC, which might be a criterion for disability prevention and could serve as an outcome measure for physical function in older people.